Inclusive Quarantine: The Pathology and Performance of Jewish Existence in the Erlangen Opinion on the Aryan Paragraph - Tafilowski, Ryan (Studies in Christian-Jewish Relations, 2016)
The Erlangen Opinion on the Aryan Paragraph, co-authored by Lutheran theologians Paul Althaus and Werner Elert, has proven controversial. Scholars have typically interpreted the document’s recommendation regarding the place of Jewish Christians in the church according to an inclusion/exclusion binary model. However, the Erlangen Opinion actually reflects a dialectical theology of Jewish existence that Althaus had developed during the Weimar years. Following this dialectic of pathology and performance, Althaus envisions neither the total inclusion nor total inclusion of Jews in the German state church. Rather, he proposes an inclusive quarantine of Jewish persons, who represent both a mortal danger to and indispensable factor for all communities—both societal and ecclesial. By probing the logic of this important artifact of Protestant theology’s complicated relationship to National Socialist ideology, the article sheds light on the ambivalent nature of Christian anti-Judaism and antisemitism.